1992
DOI: 10.1016/0014-5793(92)80966-k
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid enhances the secretion of plasminogen from cultured rat microglia

Abstract: To determine the amount of plasmmogen in microghal condmoned medium, a highly sensitive and Sl~Clfic enzyme-linked immuno~orbent assay (ELISA) for lot plasmmogen wa~ e~tablished. Weak cross-reactwity with human serum plasminogen was observed, while no re.activity was deified with frog and carp plasmmogen. The specificity of the immuno~orbent a~say was confirmed by Western blotting. The secretion of plasmmogen into the microglial culture medium was ouantlfied by using the established ELISA and was found to be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…7). We investigated the antiapoptotic activities of 1 ng/ml of IL-3, IL-6, M-CSF, bFGF, and TNF␣ and 10 µg/ml of PGn, which are produced by cultured microglial cells (Shimojo et al, 1991;Nakajima et al, 1992;Lee et al, 1993;Appel et al, 1995;Sawada et al, 1995). Figure 7 shows that PGn and TNF␣ were effective in rescuing neurons from SNP-induced neuronal apoptosis, whereas the other cytokines were ineffective.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…7). We investigated the antiapoptotic activities of 1 ng/ml of IL-3, IL-6, M-CSF, bFGF, and TNF␣ and 10 µg/ml of PGn, which are produced by cultured microglial cells (Shimojo et al, 1991;Nakajima et al, 1992;Lee et al, 1993;Appel et al, 1995;Sawada et al, 1995). Figure 7 shows that PGn and TNF␣ were effective in rescuing neurons from SNP-induced neuronal apoptosis, whereas the other cytokines were ineffective.…”
Section: Resultsmentioning
confidence: 97%
“…PGn has been a candidate for neurotrophic factors secreted by microglial cells (Nagata et al, 1993), and it was revealed to have neuroprotective activity against NO-induced injury in the present study, but a rather high concentration of PGn (10 µg/ml) was necessary to preclude neuronal apoptosis. According to the study of Nakajima et al (1992), MiCM contains PGn at concentrations less than 1 ng/ml. Moreover, the neuroprotective action of PGn was abolished completely by heat treatment.…”
Section: Discussionmentioning
confidence: 99%
“…2004a), and consequently, propagating an overly sensitive inflammatory response. Alternatively, activated microglia and apoptotic neuronal cells also synthesize PGn, in addition to tPA (Nakajima et al. 1992a,b,c; Tsirka et al.…”
Section: Enolase and Alzheimer’s Diseasementioning
confidence: 99%
“…ED-1 monoclonal antibody was obtained from Serotec (Oxford, UK). The antibody against rat plasminogen was raised in rabbits and further purified as IgG by using ImmunoPure (Pierce, Rockford, IL) (Nakajima et al, 1992b). Anti-rat/ mouse NGF receptor monoclonal antibody was purchased from Boehringer Mannheim (Germany).…”
Section: Miscellaneous Reagentsmentioning
confidence: 99%